Human genomic diversity, viral genomics and proteomics, as exemplified by human papillomaviruses and H5N1 influenza viruses - Sakharkar, Meena Kishore (2016)
The diversity of hosts, pathogens and host-pathogen relationships reflects the influence of selective pressures that fuel diversity through ongoing interactions with other rapidly evolving molecules in the environment. This paper discusses specific examples illustrating the phenomenon of diversity of hosts and pathogens, with special reference to human papillomaviruses and H5NI influenza viruses. We also review the influence of diverse host-pathogen interactions that determine the pathophysiology of infections, and their responses to drugs or vaccines.